Profiling Students’ Problem-Solving Skills through the Ethno-STEAM Approach in Elementary School Contexts - Azizah, Imarotul; Suryanti, Suryanti; Mariana, Neni (Journal of Innovation and Research in Primary Education, 2025)
This research aims to explore and describe the profile of fifth-grade students’ problem-solving abilities through the integration of an Ethno-STEAM approach at SDN Kendangsari IV Surabaya. Using a descriptive quantitative design, the study involved 18 students and focused on analyzing their performance across five problem-solving stages based on Polya's problem-solving framework: identifying the problem, generating solutions, planning and designing, implementing, and evaluating. Students were given a contextual task that integrated cultural (ethno) elements and STEAM (Science, Technology, Engineering, Arts, and Mathematics) to solve real-life environmental issues related to plastic waste in their school environment. The results revealed that 72% of students were at the Developing Level, indicating emerging capabilities in identifying problems and proposing basic solutions, yet requiring substantial teacher assistance in planning, implementation, and evaluation stages. Meanwhile, 28% reached the Proficient Level, demonstrating more independent and systematic thinking, although further support was still needed for deeper reflection and evaluation. No students reached the Excellent Level, and none remained at the Initial Level. A detailed analysis across Polya’s stages showed strong performance in problem identification (67% at Good to Excellent levels), but significant challenges in the evaluation stage, where 89% of students were categorized as "Needs Improvement." These findings suggest that metacognitive scaffolding, localized content, and collaborative projects are essential to enhance higher-order thinking skills. The Ethno-STEAM approach shows strong potential in connecting scientific concepts with students’ cultural backgrounds, encouraging both relevance and engagement in learning. However, its implementation must be supported by structured pedagogical strategies to maximize its effectiveness in elementary education contexts.